Ekspor Limbah Elektronik dari Beberapa Negara Eropa ke Ghana dalam Perspektif Imperialisme Ekologi - Gracety Fani Oktavia br Ginting; Rr. Hermini Susiatiningsih; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Exports of e-waste from several European countries to Ghana are common. The mostimpact by Ghana is the pollution of the environment which then causes the health of thepeople of Ghana to be disrupted because the toxins produced by burning electronic wasteare contaminated with the environment. On the other hand, Europe exports e-wastebecause it wants to create effectiveness and efficiency in e-waste management issues. Thisstudy aims to find out why the dimension of injustice is present in the phenomenon of ewasteexports from European countries to Ghana. The theory used to answer the problemformulation is the theory of ecological imperialism, which was coined by Alfred Crosby.The author uses the literature study method in collecting data from books,journals/articles, websites, and international news. The result of this study is that theexport of e-waste from Europe to Ghana has created a dimension of injustice that has ledto European colonization of the environment by Europe to Ghana, this is due todifferences in environmental quality, economic inequality, differences in social andcultural conditions, and implementation of regulations and inadequate policies.